1998
DOI: 10.1136/hrt.80.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of QT and QTc interval in healthy children, and effects of sinus arrhythmia on QT dispersion

Abstract: Objective-To determine the normal values of QT and QTc dispersion and the eVects of sinus arrhythmia on QT dispersion in healthy children. Patients and setting-The study was carried out in a university hospital on 372 local schoolchildren (200 male, 172 female), aged seven to 18 years. Methods-The QT and preceding RR intervals of at least one sinus beat were measured manually in a range of nine to 12 leads on standard 12 lead surface ECGs. The corrected QT interval was computed by the method of Bazett. Dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 20 publications
(15 reference statements)
2
50
0
5
Order By: Relevance
“…A recent study of children and adolescents reported a similar increased rate of prolonged QTc during daytime ECG monitoring in type 1 diabetic patients (23%) compared with matched control subjects (3%) [24]. While it may be difficult to compare QTc values between studies [11], figures from a large normative database indicate that prolonged QTc (>440 ms) is unusual in healthy children [25,26]. In our subjects, QTc was measured during sleep.…”
Section: Discussionsupporting
confidence: 53%
“…A recent study of children and adolescents reported a similar increased rate of prolonged QTc during daytime ECG monitoring in type 1 diabetic patients (23%) compared with matched control subjects (3%) [24]. While it may be difficult to compare QTc values between studies [11], figures from a large normative database indicate that prolonged QTc (>440 ms) is unusual in healthy children [25,26]. In our subjects, QTc was measured during sleep.…”
Section: Discussionsupporting
confidence: 53%
“…As in adults, data generally indicate that <5% of children have a QTc interval >450 ms. 44,79,97 In addition, as noted above, studies of siblings of children with long QT syndrome found increased risk of cardiovascular events at QTc intervals of 460 to 500 ms, though reported cases of torsades de pointes in children prescribed methadone are rare. Given the potential for increased risk and the availability of alternative opioids, the panel suggests that clinicians apply similar QTc parameters for use of methadone in children as in adults, until more evidence is available.…”
Section: Baseline Electrocardiogramsmentioning
confidence: 90%
“…Normal values of QTd are reported to be 36 Ϯ 13.7 ms in 111 healthy children 5 days to 16 years old. 24 There is increased QTd in various cardiac diseases including patients with LVH and hypertrophic cardiomyopathy. 25,26 Although the mechanism by which QTd is increased in hypertrophic cardiomyopathy remains unclear, increased QTd has been shown to be a marker of increased risk for sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%